Legiones y Falanges: Populist Press and Literature - Pinello, Ambra (Populismo y propaganda: entre el presente y el pasado, 2020)
Addressing people in order to enforce their power is a common feature of different political parties and governments, regardless of whether they are right wing or left wing, and, in this process, the press plays a crucial role. In this context, the bilingual publication Legioni e Falangi. Rivista d’Italia e di Spagna/Legiones y Falanges. Revista mensual de Italia y de España (1940–43) is a paradigmatic example. Some of the most important intellectuals of the time, including Azorín, Manuel Machado and Gerardo Diego, wrote in this magazine, facing historical reality of Fascism and Francoism and generating unexpected results.